Inseparable/IER3IP1 are essential for cytokinesis in Drosophila neuroblasts and human cells. - Kakade, A.A.; Gupta, S.; Johnson, A.; Varghese, R.; Adicherla, H.; Nagarkar-Jaiswal, S. (Proceedings of the National Academy of Sciences of the United States of America, 2025)
To unveil the molecular players that maintain neural stem cell (NSC) homeostasis, we conducted a genetic screen in Drosophila and isolated an uncharacterized gene that we named Inseparable (Insep). Insep is the Drosophila homologue of human IER3IP1, a gene associated with Microcephaly, Epilepsy, and Neonatal Diabetes Syndrome-1 (MEDS-1). We show that Insep loss leads to early larval lethality with small brains and these phenotypes can be rescued by expressing IER3IP1 indicating that their biological function is conserved through evolution. The Insep deficient neuroblasts fail to complete cytokinesis and show excessive accumulation of Rab11 vesicles in the cytoplasm. Similarly, IER3IP1 depletion in human cells leads to cytokinesis failure and accumulation of Rab11 vesicles. Insep and IER3IP1 localize to Rab11 vesicles and interact with Rab11. The pathogenic mutations in IER3IP1 perturb its localization to Rab11 vesicles. These results suggest that Insep and IER3IP1 work along with Rab11 and may regulate fusion of Rab11 vesicles to the advancing furrow during cytokinesis.